PESAN MORAL KERIS PUSAKA TRADISIONAL MASYARAKAT JAWA PADA SISWA PASRAMAN HINDU - Winarsih (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
The purpose of this study is to foster a sense of love back to Javanese culture, especially traditional heirloom krises, through the teaching of moral values contained in traditional heirloom krises. The object of this research is pasraman students. In fostering a sense of love for a culture that is almost lost requires socialisation to the community. One of them is giving lessons to pasraman students about the moral message of a traditional heirloom, namely Keris. With this learning, students are directed to preserve the tradition by forming a holistic understanding for Pasraman students about the importance of maintaining tradition, morality, and spirituality in their lives. This research uses a qualitative method with a descriptive approach used in collecting all research data through literature studies. The results of this study through learning the meaning and moral value of keris through symbols can provide knowledge to pasraman students about the meaning and moral values contained in traditional keris heirlooms. Some of the applications of the moral messages of traditional kris heirlooms by pasraman students are courage, firmness, spiritual strength and closeness to God, pride of identity and self-defence and strength. The delivery of the moral message of this kris heirloom uses several methods or approaches, namely the Visual and Practical approach, the Symbolism and Ricikan approach, the Story and Cultural Narrative approach and the Inscription Use Approach as a Moral Media. The impact of learning about the moral message of Javanese krises on the attitudes and behaviour of pasraman students can increase the value of simplicity and humility, foster respect and cultural pride, foster awareness of ethics and morality, the most important thing in this study is to educate and direct students to strengthen student character with three elements, namely tradition, morality and spirituality. The integration of these three elements can form a holistic understanding for Hindu Pasraman students about the importance of maintaining tradition, morality, and spirituality in their lives.